The relationship between perfectionism and marital outcomes: a systematic review and meta-analysis - Hadian Hamedani, Kiana; Majzoobi, Mohammad Reza; Forstmeier, Simon (Frontiers in Psychology, 2024)
Perfectionism, as a transdiagnostic variable, can influence both the intrapersonal and interpersonal domains, one of the most significant of them is thought to be marital relationship. Given that perfectionism within a couple can negatively affect their intimate relationship and potentially lead to destructive outcomes, reviewing studies conducted in this area seems to be essential to gain a clearer understanding. Therefore, the present systematic review aims to examine the association between perfectionism and marital outcomes in married individuals. To this end, a comprehensive search was conducted across major scientific databases, including APA PsycArticles, PubMed, and Web of Science, using specific keywords and Boolean operators. Included were the English-Language studies published between 1980 and 2023 that investigated the relationship between perfectionism and marital outcomes in heterosexual couples. Out of the studies identified, 23 met the inclusion criteria for this review, of which 16 studies met the criteria for meta-analysis. The meta-analysis indicated a small-to-moderate effect size for the association between perfectionism and marital outcomes (r=.26). Given the importance of marital relationship, such effect sizes for variables which may influence marital relationship bears significant value. Therefore, the findings may encourage researchers to conduct various studies to examine specific details, moderators, and mediators in the relationship between perfectionism and marital outcomes and may also prompt couple therapists to address perfectionism as a destructive factor and integrate strategies into their protocols to reduce its impact in intimate relationships.